2010
DOI: 10.1051/agro/2010015
|View full text |Cite
|
Sign up to set email alerts
|

Improved efficiency of soil solarization for growth and yield of greenhouse tomatoes

Abstract: -Soil solarization is a pre-planting treatment not based on chemicals, used in hot climates to control weeds and soil-borne pathogens. Its effectiveness has been widely demonstrated, for example, in the USA, Spain, Portugal, Egypt, Italy, Mexico, India and Iraq. However, an improvement in efficacy is needed before it can be widely adapted as a commercial practice. Supplementation of the soil with organic matter prior to solarization has been proposed as a management option, but its effectiveness has yet to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 23 publications
2
20
1
1
Order By: Relevance
“…The results obtained here are consistent with the reduction of mite populations in gladioli and garlic fields (Gerson & Smiley 1990) and onion fields (Ono et al 1993) following solarisation treatment. Furthermore, Mauromicale et al (2010) suggested solarisation as a useful and environmentally friendly soil-disinfestation method that increases the yield of tomatoes. More recently, Gill et al (2017) have reviewed the benefits of solarisation for pest control of crops in various parts of India.…”
Section: Results and Discussion E Ects Of Solarisation Treatmentmentioning
confidence: 99%
“…The results obtained here are consistent with the reduction of mite populations in gladioli and garlic fields (Gerson & Smiley 1990) and onion fields (Ono et al 1993) following solarisation treatment. Furthermore, Mauromicale et al (2010) suggested solarisation as a useful and environmentally friendly soil-disinfestation method that increases the yield of tomatoes. More recently, Gill et al (2017) have reviewed the benefits of solarisation for pest control of crops in various parts of India.…”
Section: Results and Discussion E Ects Of Solarisation Treatmentmentioning
confidence: 99%
“…Mauromicale et al [44] reported an increase in tomato yield (up to 70% depending on treatment) when organic matter composed of cow dung, poultry manure and leather was incorporated into the soil prior to solarization. Again, Mauromicale et al [16] found that the addition of compost based on cattle or horse manure prior to solarization (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that incorporating organic materials can improve the nutrient status of the soil and promote higher levels of microbial population and activity . In Mediterranean greenhouse tomato crops it has been demonstrated that organic supplementation prior to solarization promotes a long lasting increase (up to 9 months) in total N, exchangeable K 2 O and available P 2 O 5 content within the soil, thereby enhancing growth and developmental processes and yield, through a more favorable source-sink balance of the plant (Mauromicale et al, 2010). In our experiment, organic supplementation showed a strong synergistic effect with soil solarization in affecting the viability of broomrape seedbank, so that this was annulled already by combining 0.35 kg m −2 of organic supplementation and a single cycle of soil solarization.…”
Section: Discussionmentioning
confidence: 99%
“…Such effect can be attributable in part to the increased thermal regime of solarized soil recorded in response to organic supplementation. However, it must pointed out that the effects of soil solarization against soil-borne pathogens and parasites also depend on the increased concentration of volatile toxic compounds within the soil, and that this effect is amplified by biologically-active molecules released upon a heatdriven decay of organic amendments during solarization (Katan, 1981;Gamliel, 2000;Mauromicale et al, 2010). The results of the present experiment suggests that combining organic amendment and soil solarization, beyond increasing greenhouse tomato yield, could have a pivotal role in developing more efficient farm-scale programs aimed at both eradicating broomrape seedbank and safeguarding long-term soil fertility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation